PROCESSUS D’ENGAGEMENT DES PREMIÈRES NATIONS, MÉTIS ET INUITS DANS LA RÉVISION DU CURRICULUM ONTARIEN - St-Pierre, Joannie (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2019)
Ces notes de terrain décrivent le processus de révision du curriculum ontarien qui s’arrime avec les appels à l’action de la Commission de vérité et réconciliation du Canada. En résumant un entretien avec une agente d’éducation du Ministère de l’éducation de l’Ontario, ce texte dresse le portrait du plan d’action mis en place pour répondre aux appels à l’action et dans lequel les Premières Nations, Métis et Inuits sont engagés. THE PROCESS OF ENGAGING FIRST NATIONS, MÉTIS AND INUIT IN THE REVISION OF ONTARIO’S CURRICULUM This Note from the Field aims to describe the Ontarian curriculum review process related to the Calls to Action identified by the Truth and Reconciliation Commission of Canada. By summarizing an interview with an education officer from the Ontario Ministry of Education, this text outlines the actions undertaken in order to respond to the Calls to Action in which First Nations, the Métis and Inuit Peoples are engaged.